Effects of Long-Term Treatment with Different Types of Anti-Epileptic Drugs on Vitamin D2 and Osteoprotegrin Serum Levels in Iraqi Patients - Sara jafer, Shatha H Ali, Ali M.A. Al-Nuaimi (Pakistan Journal of Medical & Health Sciences, 2022)
Epilepsy is a chronic neurological illness had been described as repeated seizures associated with abnormal neurological activities in the brain. Epilepsy affects nearly fifty million people worldwide, with 85 percent of them living in developing countries. Vitamin D2 (VD2) is ergocalciferol (made from ergosterol). Genetic disorders related to vitamin D metabolism are dysfunction of generally loss osteoid mineralization the leading cause to bone disorders including: rickets or osteomalacia. Osteoprotegerin (OPG) is an osteoclastogenesis inhibitory factor (OCIF), OPG has essential role in bone metabolism and bone mass level. The aim of the present study is to investigate the effects of long-term treatment with anti-epileptic drugs (old Vs new antiepileptics) on vitamin D2 and osteoprotegrin levels among Iraqi epileptic patients. The study included fifty-one epileptic outpatients, whom attending the Consultant Clinic of Baghdad Teaching Hospital at the Medical City –Complex for the period from October/2021 to December/2021. The selected patients were on antiepileptic drugs for more than 2years, hence were grouped according to their antiepileptic therapy into: Group-1: 24 epileptic patients on old antiepileptic drugs (Carbamazepine or Valproate). Group-2: 27 epileptic patients on new antiepileptic drugs (Levetiracetam), to be compared with Group-3: 28 apparently healthy control subjects, with age and sex matching to that of patients. Serum was obtained from their blood specimens to measure: serum VD2 and OPG concentrations among the study groups participants, using specific ELISA Kits. Data analysis revealed that the mean vitamin D2 levels were not significantly different between group -1 (old antiepileptic drugs) and group-2 (new antiepileptic drugs), whereas, both of the patients groups expressed significantly lower values than the control group. However, serum osteoprotegrin levels were significantly elevated in group-1 compared to group-2. Furthermore, both of the epileptic patients groups had significantly higher values compared to the healthy subjects group.